The simulation of Single-Phase Induction Motor (SPIM) operation using Insulated-Gate-Bipolar Transistors (IGBT) AC/DC/AC converter: article / Fazarudin A. Wahab - A. Wahab, Fazarudin (2011)
This paper describes a generalized simulation model of a single-phase induction motor (SPIM) using SIMULINK software package of MATLAB. An analysis of SPIM performance using power electronics application is studied. The installation of power electronics can save energy consumption of electrical apparatus with more efficient use of electricity. Insulated-Gate Bipolar Transistor (IGBT) was used as a switching device for both rectifier and inverter part. The. IGBT has low switching times as well as low power losses and thus can make better performance. Sinusoidal Pulse Width Modulation (SPWM) technique was used to switch on or off the IGBTs in both converter circuits. The switching frequency in the PWM generator for IGBTs was adjusted and determined. Speed performance of the SPIM using AC/DC/AC converter and directly connected to AC supply was observed. The percentages of Total Harmonic Distortion (THD) of the input and output current that comply with IEEE 519-1982 were obtained after adjusting filter value and the switching frequency